Peningkatkan Aktivitas dan Hasil Belajar Peserta Didik melalui Penerapan Model Problem Based Learning Berbantuan Wordwall - Puspita Zakiya Mumtaza; Ardi Ardi; Elvira Elvira; Muhyiatul Fadilah; Suci Fajrina (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to enhance students' learning activities and outcomes through the implementation of the Wordwall assisted Problem Based Learning (PBL) model in the Ecosystem topic for Phase E at SMA N 1 Nan Sabaris. The research was conducted at SMAN 1 Nan Sabaris in class X.E.5 during the even semester of the 2024/2025 academic year, with 36 students as subjects. This study is a classroom action research consisting of two cycles, each comprising two sessions. Each cycle follows four stages: planning, implementation, observation, and reflection, using the Wordwall-assisted Problem-Based Learning model. Data on students' learning activities and outcomes were collected based on observation sheets of learning activities and student learning outcome tests. The application of the Wordwall-assisted Problem-Based Learning (PBL) model proved effective in improving students' learning activities and outcomes in the Ecosystem topic. This success was demonstrated by increased participation and enthusiasm among students during the learning process. Learning outcomes improved by 45%. This increase indicates that the corrective measures taken, such as adding instructional videos and modifying Wordwall games, successfully enhanced students' understanding and mastery of the material.